1987
DOI: 10.1055/s-2006-962803
|View full text |Cite
|
Sign up to set email alerts
|

Plant Based Antiamoebic Drugs; Part I. Antiamoebic Activity of Phenanthroindolizidine Alkaloids; Common Structural Determinants of Activity with Emetine

Abstract: Fourteen phenanthroindolizidine alkaloids which differ in number, nature, and distribution of oxygen-bearing substitucnts, in the presence of unsaturation in ring E or in the presence of an angular (methyl or hydroxyl) function or in the cleaved phenanthrene portion were isolated from two species of Tylophora plant. These along with the synthesized unsubstituted molecule and its intermediates were examined for their amoebicidal activity in vitro and all had been found active with varying MIC's. Structure-activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…The leaves of this plant have been used for the treatment of asthma as well as bronchitis, rheumatism and dysentery in India. These alkaloids possesses anticancer [20-24], anti-inflammatory [19,25], anti-ameobicidal [26] and anti-viral [27] activity. Several key metabolic enzymes, including thymidylate synthase [28] and dihydrofolate reductase have been reported as biological targets of tylophorine alkaloids [29].…”
Section: Introductionmentioning
confidence: 99%
“…The leaves of this plant have been used for the treatment of asthma as well as bronchitis, rheumatism and dysentery in India. These alkaloids possesses anticancer [20-24], anti-inflammatory [19,25], anti-ameobicidal [26] and anti-viral [27] activity. Several key metabolic enzymes, including thymidylate synthase [28] and dihydrofolate reductase have been reported as biological targets of tylophorine alkaloids [29].…”
Section: Introductionmentioning
confidence: 99%
“…So far, reported alkaloids from Tylophora hirsuta are 13 a-methylo-hirsutine, tylohersutinine, 13a-methyltylo-hirsutinidine and tylohirsutinidine [8,9]. In 1987, Bhutani et al reported its anti-amoebic activity [10]. Other reported constituents from the aerial parts of the Tylophora hirsuta are Gymnorhizol, and β-sitosterol [11].…”
Section: Introductionmentioning
confidence: 99%
“…The biological properties of these alkaloids range from cancer cell growth inhibition ( in vitro and in vivo ) [1, 916] and anti-inflammatory [3, 17] activity to anti-ameobicidal [18] and anti-viral [19] activity. A summary of their GI 50 concentrations in various cancer cell lines is given in Table 1.…”
Section: Introductionmentioning
confidence: 99%